Awareness and utilization of social security scheme and other government benefits by the elderly – A study in rural area of district Dehradun - Srivastava, Ashok Kumar; Kandpal, S D (Indian Journal of Community Health, 2014)
Background: The rapid ageing of India’s population, has highlighted the need for better economic security arrangements for the elderly. Increased longevity is making care of the elderly more expensive and traditional family ties are beginning to fray, and The Government of India have initiated an array of schemes and benefits for providing some level of social security to the elderly. Objectives: To study the background characteristic of the elderly and extent of awareness and utilization of social security and other government benefits. Methodology: Study Design: Descriptive, observational cross sectional field based study. Statistical analysis: Percentages and proportions. Results: Three out of every five houses was headed by an elderly. No formal education was received by 35.4% of the elderly. Widowhood was as high as 49.5% among elderly women. Awareness of social security scheme (Indira Gandhi National Old Age Pension Scheme) was observed in 74.6% of the elderly but only 45.4% utilized it. The proportion of elderly who were aware of concession in railway ticket and higher interest rates on deposits in Bank/Post office respectively was 34.9% and 32.9%. The utilization rate was however abysmally low with 27.8% utilizing railway ticket concession and 10.1% depositing money to get higher interest in Bank/Post office. Less than 1% elderly utilized income tax benefits. Conclusion: There is an urgent need to review the existing policy guidelines and amend them to suit and benefit the elderly. The schemes and benefits meant for the elderly needs to be more relevant and effectively implemented at the community level.